Bionic Microbubble Neutrophil Composite for Inflammation- Responsive Atherosclerotic Vulnerable Plaque Pluripotent Intervention - Liu Fangfang; Mao Yang; Yan Jiaqi; Sun Yu; Xie Zhihua; Li Fei; Yan Fei; Zhang Hongbo; Zhang Pengfei (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
Rupture or erosion of inflammatory atherosclerotic vulnerable plaque is essential to acute coronary events, while the target intervene of vulnerable plaque is very challenging, due to the relatively small volume, high hemodynamic shear stress, and multifactorial nature of the lesion foci. Herein, we utilize the biological functionality of neutrophil and the versatility of microbubble in the acoustic field, to form Neu-balloon through CD11b antibody binding. The Neu-balloon inherits the advantage of neutrophils on firming the endothelium adhesion even at shear stress up to 16 dyne/cm(2) and also maintains the acoustic enhancement property from the microbubble, to accumulate at atherosclerotic lesions under acoustic in an atherosclerotic Apo E-/- mice model. Interestingly, Neo-balloon also has high and broad drug loading capacity, which enables the delivery of indocyanine green and miR-126a-5p into vulnerable plagues in vivo. Overall, the bionic Neu-balloon holds great potential to boost on-demand drug transportation into plaques in vivo.